Investment safety of Kazakhstan - Tulebayeva, G. A. (Journal of Economic Research & Business Administration, 2015)
The article is concept of economic security of Kazakhstan in general world of globalization and post-crisis development. Along with the positive trends discussed the threats the national security of the investment and economic indicators for their definitions, such as the poor state of fixed assets, low investment activity, the crisis in innovative potential and so on. Determined the essence of the concept of “investment security” and its main criteria. Identified the main directions and instruments of public policy to ensure investment security requirements as a condition for of stable development and modernization of Kazakhstan’s economy.